2009
DOI: 10.1002/hep.23128
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Hepatic Encephalopathy Is Associated with Motor Vehicle Crashes

Abstract: M inimal hepatic encephalopathy (MHE) is a prevalent neurocognitive complication of cirrhosis that is diagnosed in up to 80% of patients with cirrhosis. It is associated with increased progression to overt hepatic encephalopathy (OHE) and impaired driving skills. 1-3 MHE patients have impaired attention, visuomotor coordination, psychomotor speed, and response inhibition. 4 Paper-pencil standard psychometric tests (SPT) or the computerized inhibitory control test (ICT) can be used to diagnose MHE. 5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
234
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 286 publications
(249 citation statements)
references
References 28 publications
6
234
2
2
Order By: Relevance
“…64,65 Studies have consistently shown that patients with MHE have a diminished quality of life, cognitive function, daily function, and driving impairment. [3][4][5][6][7][8][9][10] While it was once thought that cognitive impairment with CHE or OHE was reversible, data from studies evaluating medical treatment or liver transplantation suggest that the associated cognitive changes may not be totally reversible. [66][67][68] Moreover, it has been demonstrated that even after therapy and improvement to normal mental status, a single episode of OHE may continue to have residual negative effects on cognitive function.…”
Section: Management Guidelines For Covert Hepatic Encephalopathymentioning
confidence: 99%
See 2 more Smart Citations
“…64,65 Studies have consistently shown that patients with MHE have a diminished quality of life, cognitive function, daily function, and driving impairment. [3][4][5][6][7][8][9][10] While it was once thought that cognitive impairment with CHE or OHE was reversible, data from studies evaluating medical treatment or liver transplantation suggest that the associated cognitive changes may not be totally reversible. [66][67][68] Moreover, it has been demonstrated that even after therapy and improvement to normal mental status, a single episode of OHE may continue to have residual negative effects on cognitive function.…”
Section: Management Guidelines For Covert Hepatic Encephalopathymentioning
confidence: 99%
“…Over the last decade, there is compelling evidence that MHE has a negative impact on quality of life and patient well being. [3][4][5][6][7][8][9][10] However, the natural history of CHE and the effect of treatment on the overall prognosis of CHE requires further long-term studies.…”
Section: Management Guidelines For Covert Hepatic Encephalopathymentioning
confidence: 99%
See 1 more Smart Citation
“…4 After measuring cognition with a brief psychometric test battery, and the inhibitory control test (ICT), the drivers were assigned to either the MHE cohort or the non-MHE cohort. Collision and violation data were collected by self-report and from the Department of Transportation for the year before and the year after the psychometric testing.…”
mentioning
confidence: 99%
“…ICT appeared to be more sensitive than the standard psychometric battery in the diagnosis of MHE. 4 Similar criteria were used as in a prior report for the case definition of MHE: Ͼ2 standard deviations for any two of the four psychometric tests or Ͼ 5 lures on the ICT. 5 Yet, the psychometric battery was slightly different in this study than in their prior work.…”
mentioning
confidence: 99%